Eco-epidemiology and genetic characterisation of Toxoplasma gondii in wildlife landscapes in the Greater Kruger, South Africa - Morar-Leather, Darshana (University of Pretoria, 2025)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2024.